2012
DOI: 10.1111/j.1600-0765.2012.01472.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cigarette smoke and nicotine on cell viability, migration and myofibroblastic differentiation

Abstract: Cigarette smoke condensate may stimulate cell survival and migration at low concentrations and inhibit these cell responses at higher levels of exposure. Moreover, CSC may interfere in myofibroblastic differentiation.These results show that cigarette smoke, but not nicotine, may significantly alter cell viability, cell migration and myofibroblastic differentiation in gingival mesenchymal cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 41 publications
4
45
1
Order By: Relevance
“…First, we analyzed the metabolic activity of HGFs when exposed to different fluid concentrations for times up to 72 h. Our results suggested an extreme toxicity for concentrations higher than 1 mg/mL just after 24 h. Afterwards, we deepened the investigation of the effects of 1 mg/mL, very close to the widely used 5 mM nicotine concentration reported in many studies about nicotine effects on HGFs [10,24,28], that it has been demonstrated to be the nicotine concentration present in the saliva of the smokers [29]. MTT results indicated also a high toxicity after 72 h for all the concentrations tested; therefore, the other parameters were evaluated at earlier experimental times.…”
Section: Discussionmentioning
confidence: 87%
“…First, we analyzed the metabolic activity of HGFs when exposed to different fluid concentrations for times up to 72 h. Our results suggested an extreme toxicity for concentrations higher than 1 mg/mL just after 24 h. Afterwards, we deepened the investigation of the effects of 1 mg/mL, very close to the widely used 5 mM nicotine concentration reported in many studies about nicotine effects on HGFs [10,24,28], that it has been demonstrated to be the nicotine concentration present in the saliva of the smokers [29]. MTT results indicated also a high toxicity after 72 h for all the concentrations tested; therefore, the other parameters were evaluated at earlier experimental times.…”
Section: Discussionmentioning
confidence: 87%
“…Studies have proved its role as a risk factor for higher occurrence of bone fractures, 31 increased periodontal destruction, 32,33 decreased density of oral and wholebody bones, 34 and, in regard to oral implant therapy, decreased bone-to-implant contact 35 and greater marginal bone loss around implants. Although several studies have tried to understand how tobacco and its metabolites affect these conditions, there is no clinical study assessing the gene expression of bone-related markers in alveolar tissue harvested from smokers.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we employed a nested collagen matrix model (developed in 2006) to investigate fibroblast migration/motility (Grinnell et al, 2006). The nested collagen matrix model is an easy, rapid, reliable and quantitative method for measuring the migration of cell populations in 3D matrices (Grinnell et al, 2006;Miron-Mendoza et al, 2008;Zhou and Petroll, 2010;Kim et al, 2012;Silva et al, 2012). A molecular method (siRNA) was used to confirm the role of the MCP-1/CCR2 axis in silicosis.…”
Section: Discussionmentioning
confidence: 99%